ANSID: A Solid-Phase Proteomic Approach for Identification and Relative Quantification of Aromatic Nitration Sites - Nuriel, Tal; Whitehouse, Julia; Ma, Yuliang; Mercer, Emily J.; Brown, Neil; Gross, Steven S. (Frontiers in Chemistry, 2016)
Nitration of tyrosine and other aromatic amino acid residues in proteins occurs in the setting of inflammatory, neurodegenerative and cardiovascular diseases – importantly, this modification has been implicated in the pathogenesis of diverse diseases and the physiological process of tissue aging. To understand the biological consequences of aromatic nitration in both health and disease, it is critical to molecularly identify the proteins that undergo nitration, specify their cognate modification sites and quantify their extent of nitration. To date, unbiased identification of nitrated proteins has painstakingly employed 2D-gel electrophoresis followed by Western Blotting with an anti-nitrotyrosine antibody for detection. Apart from being relatively slow and laborious, this method suffers from limited coverage, the potential for false-positive identifications and failure to reveal specific amino acid modification sites. To overcome these shortcomings, we have developed a solid-phase, chemical-capture approach for unbiased and high-throughput discovery of nitrotyrosine and nitrotryptophan sites in proteins. Utilizing this method, we have successfully identified several endogenously nitrated proteins in rat brain and a total of 244 nitrated peptides from 145 proteins following in vitro exposure of rat brain homogenates to the nitrating agent peroxynitrite (1 mM). As expected, Tyr residues constituted the great majority of peroxynitrite-mediated protein nitration sites; however, we were surprised to discover several brain proteins that contain nitrated Trp residues. By incorporating a stable-isotope labeling step, this new Aromatic Nitrtion Site IDentification (ANSID) method was also adapted for relative quantification of nitration site abundances in proteins. Application of the quantitative ANSID method offers great potential to advance our understanding of the role of protein nitration in disease pathogenesis and normal physiology.